Ethics In Business Law: A Paternalistic Legal Philosophy Approach From John Stuart Mill - Suputra, I Dewa Gde Ery; Kurniawan, I Gede Agus; Gorda, Anak Agung Ayu Ngurah Sri Rahayu (Faculty of Law, Universitas Pattimura, 2025)
Introduction: In the modern business world, John Stuart Mill's paternalistic legal philosophy, especially the